Thrombocytopenia and neonatal outcomes among extremely premature infants exposed to maternal hypertension. Issue 2 (7th December 2022) - Delaney, Joanne; Nunes, Gabriela De Carvalho; Simoneau, Jessica; Beltempo, Marc; Malhamé, Isabelle; Goudie, Catherine; Altit, Gabriel
Abstract: Background: Hypertensive disorders of pregnancy (HDP) are associated with neonatal hematological disturbances, such as thrombocytopenia. The association of HDP to platelet counts in the context of extreme prematurity, to trends of platelet counts during neonatal hospitalization, and to frequency of platelet transfusions remain to be explored. Procedure: Retrospective study of infants born at less than 29 weeks born between 2015 and 2019. Platelet counts were collected on initial complete blood count, at 2 weeks, 32 weeks post‐menstrual age (PMA), 36 weeks PMA, and closest to discharge. We examined the association between HDP and platelet counts at each time point, frequency of platelet transfusions and intraventricular hemorrhage (IVH) grade 3 or more. Results: Total 296 infants were included, 43 exposed to HDP. Infants exposed had lower platelet counts at each time point, as well as a higher prevalence of platelet less than 150 × 10 9 /L on one of the time points (32% vs. 65%, p < .001). Infants exposed to maternal hypertension were more frequently exposed to platelet transfusions (63% vs. 18%, p < .001). Mixed effect model demonstrated an association between HDP and a lower trend in platelet counts at each time point (β = −94 × 10 3 /μl, p < .001). Although initial platelet count was associated with severe IVH, it was not associated to exposure to HDP. Conclusion: Premature infants exposed to HDP have a higher prevalence of thrombocytopenia, increased frequency of platelet transfusion, and an altered trend in platelet counts during neonatal hospitalization.